The physical, mental, and emotional health of older people who are living alone or with relatives. - You KS; Lee H (Archives of Psychiatric Nursing, 2006)
In Korea, as in other countries, the number of older adults is growing substantially, and the proportion of older adults is projected to be 14.3% by 2022 [Ministry of Health and Social Affairs, Republic of Korea. (2003). Yearbook of health and social affairs statistics for 2003, vol. 49. Seoul, Korea: Government Printing Office]. The number of older people who are living alone in rural areas has been sharply increasing as a result of the migration of younger adults to urban areas for employment. However, information on the health status of elders who live alone is limited. Therefore, the purpose of this study was to compare the physical, mental, and emotional health status of elders who are living alone and those living with relatives in rural areas in South Korea. A cross-sectional survey design was used, and data were collected by interviewing subjects. A two-stage cluster sampling process was utilized for those living alone (n = 110) and those living with family members (n = 102). Both groups were enrolled in KyungRo-Dangs (senior centers), which are like community centers in the province. The results indicate that elders who are living with relatives scored significantly higher on several physical and mental health parameters than elders who are living alone. However, elders who are living with relatives had a significantly higher emotional health status in almost every item than elders who are living alone. These findings suggest that interventions to increase health status, especially the emotional health of elders who are living alone, are imperative and that the intervention should be sensitive to changes in the social structure of elders who are living alone in rural areas. Further studies are needed to understand the factors that are associated with the physical, mental, and emotional health of elders who are living alone and those who are living with relatives. Copyright © 2006 by Elsevier Inc.